SEQUESTRATION OF ERYTHROCYTE INFECTED BY Plasmodium berghei ANKA IN MICE LIVER TREATED WITH ETHANOL EXTRACT OF PEARL GRASS (Hedyotis corymbosa (L.) Lamk) - Nabilla Feirizky Chairunnisa; Jelita Aprisano Putri; Heny Arwati (Journal of Vocational Health Studies, 2025)
Background: Malaria is a parasitic infection caused by the Plasmodium genus. Certain Plasmodium species can evade the immune system by sequestering internal organs, including the liver. The ethanolic extract of pearl grass (Hedyotis corymbosa (L.) Lamk) (EEPG) has been reported to have an antimalarial activity in reducing parasitemia and hepatomegaly in Plasmodium berghei ANKA-infected mice. Purpose: To analyze the effect of EEPG administration on the sequestration of P. berghei ANKA-infected erythrocytes in the livers of BALB/c mice. Method: P. berghei ANKA-infected mice were treated with EEPG at doses of 250, 300, and 350 mg/kg BW. The positive and negative control groups received dihydroartemisinin-piperaquine (DHP) 187.2 mg/kgBW and 1% CMCNa, respectively. The treatments were administered for four consecutive days, followed by observation of parasitemia on Giemsa-stained tail blood smears. On day five, mice were sacrificed for liver removal. Sequestrations were observed on HE-stained slides of mouse livers. The differences in sequestration between treatment groups were analyzed using One-way ANOVA and Games-howell post-hoc analysis. The correlation between parasitemia and sequestration was analyzed using the Pearson correlation test. Result: The percentage reduction of the number of infected erythrocyte sequestration in EEPG-treated groups was 81.74%, 77.72%, and 77.70%, respectively, while the positive control group was 91.14%. Parasitemia was correlated with the number of erythrocytes sequestration (p-value < 0.05). Conclusion: EEPG was able to decrease parasitemia along with the decrease in the number of infected erythrocytes sequestration in the liver. These results indicated that EEPG is a potential source of natural antimalarial drugs, especially for reducing sequestration in the liver.